Downregulation of long noncoding RNA HCP5/miR-216a-5p/ZEB1 axis inhibits the malignant biological function of laryngeal squamous cell carcinoma cells - Zhang, Sen; Huangfu, Hui; Zhao, Qinli; Li, Yujun; Wu, Lina (Frontiers in Immunology, 2022)
Previous studies find that long noncoding RNA human leukocyte antigen complex P5 (HCP5) is regarded as an oncogene via accelerating cancer cell growth, invasion, metastasis, vascularization, and drug resistance in renal cell carcinoma, gastric cancer, and colorectal cancer. Nevertheless, the effect and regulatory mechanism of HCP5 in laryngeal squamous cell carcinoma (LSCC) remains unknown. In this study, HCP5 expression levels were confirmed to be prominently raised in LSCC cell lines. HCP5 knockdown reduced cell proliferation and migration and invasive ability of LSCC cell lines. Furthermore, miR-216a-5p was confirmed to sponge HCP5, and its expression was prominently downregulated in LSCC cell lines and upregulated in HCP5-silenced LSCC cell lines. miR-216a-5p overexpression downregulated the cell proliferation and migration and invasive ability of LSCC cells. Additionally, the protein level of zinc finger E-box binding homeobox 1 (ZEB1), one target gene of miR-216a-5p, was highly expressed in LSCC cell lines, and its expression level was downregulated by HCP5 knockdown and miR-216a-5p overexpression. An miR-216a-5p inhibitor reversed the effect of HCP5 knockdown on the proliferation and migration and invasive ability of LSCC cells. In conclusion, knocking down HCP5 may be a strategy to suppress the malignant biological function via regulating miR-216a-5p/ZEB1. Therefore, HCP5 may become a prospective therapeutic target for LSCC.